Bibliography: terrorism by Country – United States - Tinnes, Judith (Perspectives on terrorism, 2021)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on terrorism affecting the United States. It covers terrorist activity by international and home-grown perpetrators regardless of their ideological affiliation. The compilation focuses on recent publications (up to July 2021) and should not be considered as exhaustive. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. Additionally, full-text and reference retrieval systems have been employed to broaden the search.